High Patient Satisfaction after Inflatable Penile Prostheses Implantation Correlates with Female Partner Satisfaction. (12th September 2013) - Vakalopoulos, Ioannis; Kampantais, Spyridon; Ioannidis, Stavros; Laskaridis, Leonidas; Dimopoulos, Panagiotis; Toutziaris, Chrysovalantis; Koptsis, Michail; Henry, Gerard D.; Katsikas, Vasileios
Abstract: Introduction: Patient and female partner satisfaction after implantation of an inflatable penile prosthesis (IPP) assessed by objective means, and the correlation between the partners, is important for determining postoperative sexual life. Aim: The primary goal was to evaluate patients' erectile function and patients' and their partners' satisfaction after IPP implantation. A secondary aim was to investigate potential determinative factors of satisfaction according to device characteristics, demographics, and cause of erectile dysfunction (ED). Methods: Ninety patients, who underwent IPP implantation as an alternative to refractory or undesirable medical treatment for ED, were evaluated. Patients who could not or refused to participate, or were out of a relationship, were excluded. The 69 remaining patients were evaluated for their pre‐ and postoperative erectile function and posttreatment satisfaction for themselves and their partners. Main Outcome Measures: Preoperative and postoperative scores on the International Index of Erectile Function Questionnaire–five items (IIEF‐5) were compared. The Erectile Dysfunction Inventory of Treatment Satisfaction (EDITS) was given to males and their female partners. Patient demographics, etiology of ED, and implant characteristics were correlated also with patients' EDITS scores. Results: Mean IIEF‐5 scores demonstrated a significant improvement after IPP implantation: from 8.88 ± 3.75 to 20.97 ± 4.37 ( P < 0.001). The mean patients' EDITS score was 75.48 ± 20.54, whereas mean female partners' score was 70.00 ± 22.92, highlighting high posttreatment satisfaction for both. Regression analysis suggested a direct linear correlation of satisfaction between the sexual partners as a degree of satisfaction. There were no statistically significant differences according to level of education or implant characteristics. Concerning the etiology of ED, no conclusions could be made. Conclusions: Overcoming previous limitations in determining post‐IPP implantation satisfaction, our study reiterates high rates of patient and partner satisfaction. Of particular note, patient satisfaction appears independent of prosthesis type and cylinder length.Vakalopoulos I, Kampantais S, Ioannidis S, Laskaridis L, Dimopoulos P, Toutziaris C, Koptsis M, Henry GD, and Katsikas V. High patient satisfaction after inflatable penile prostheses implantation correlates with female partner satisfaction. J Sex Med 2013;10:2774–2781.